KONSEPSI PEMIKIRAN ISLAM DAN DEMOKRASI MENURT ABDURAHMAN WAHID - Hartono Hartono (Al-Rabwah, 2019)
Reading the thoughts of Abdurrahman Wahid or Gus Dur, each of us will be invited to enter such a large-visionary space. However, at least reading Gus Dur can be seen in Indonesian-ness (Democracy), Islam and Humanity. Islam and democracy still according to him are also competent to interact with each other so as to be able to realize a democratic democracy rather than merely procedural democracy. Dissecting the discourse of Islam and democracy certainly cannot be separated from the stage of political, state, power and government struggles on the one hand, and the relationship between Islam and other entities outside of Islam, on the other hand. The intended Islam is not a single and shared basis of values and teachings. Islam can only be seen and felt from the expressions of its adherents. Precisely because Islam can only be seen and felt from the expressions of its adherents, then Islam too is sure to have many faces. If Islam has many faces, then the political expression of Islam, of course, is very diverse. Islam is sometimes in line with democracy, but sometimes it is also opposite. At least, this is an important point and a lesson that we can take after examining books whose themes touch each other, although it cannot be said to be exactly the plot of the story and its contents.